ANALYSIS OF MARKETING STRATEGIES TO INCREASE SALES AT STORES IN LAMONGAN REGENCY - Sutri Handayani; Noer Rafikah Zulyanti (Bajang Institute, 2023)
The purpose of this study was to find out the strategy carried out by shops in Lamongan Regency in order to increase sales of their clothing products, where this is to get consumer satisfaction and profit from sales that have been made, the output of the seller will get increased sales of clothes in the form of shirts, pants, and oversized jackets. In research using qualitative research. The type of research used is the descriptive method, the object of research is one of the shops in e-commerce which is a large clothing store. The results of the study show that the 7P marketing mix is ​​the basis for shops in Lamongan Regency to market their clothes, so that they can satisfy consumers. Based on the SWOT matrix that has been carried out, it is described through SO, consumers can make clothes according to the basic materials and models they want. WO because the price of cloth is unpredictable, so sometimes the seller doesn't get too much profit. ST in the form of advertising prices contained in e-commerce. WT in the form of ordering a certain amount will get an attractive discount from the shop in Lamongan Regency